2014
DOI: 10.12989/mwt.2014.5.2.123
|View full text |Cite
|
Sign up to set email alerts
|

A review of nanomaterials based membranes for removal of contaminants from polluted waters

Abstract: Safe water has becoming a competitive resource in many parts of the world due to increasing population, prolonged droughts, climate change etc. The development of economical and stable materials and methods for providing the fresh water in adequate amounts is the need of the water industry. Nanomaterials have unique characteristics e.g., large surface areas, size, shape, and dimensions etc. that make them particularly attractive for removing various contaminants from polluted waters. Nanotechnology based multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 259 publications
(242 reference statements)
0
7
0
Order By: Relevance
“…It is estimated that approximately 50 million to 60 million people of Pakistan use arsenic contaminated groundwater. This number is alarmingly high and demonstrates the urgent need for verification and testing of all drinking water wells in the Indus Plain, followed by appropriate mitigation measures (Podgorski et al, 2017;Amin and Alazba, 2014). The purpose of this study was to develop and analyze the performance of an arsenic removal unit for elimination of arsenic contaminants from groundwater using locally available costeffective materials.…”
Section: Methods Of Arsenic Removalmentioning
confidence: 99%
“…It is estimated that approximately 50 million to 60 million people of Pakistan use arsenic contaminated groundwater. This number is alarmingly high and demonstrates the urgent need for verification and testing of all drinking water wells in the Indus Plain, followed by appropriate mitigation measures (Podgorski et al, 2017;Amin and Alazba, 2014). The purpose of this study was to develop and analyze the performance of an arsenic removal unit for elimination of arsenic contaminants from groundwater using locally available costeffective materials.…”
Section: Methods Of Arsenic Removalmentioning
confidence: 99%
“…It is well-known that biomacromolecules have the potential to become fine adsorbents for the removal of heavy metals [47,48]. Particularly, protein molecules contain numerous groups with lone pairs of electrons and partial negative charges, and these groups allow protein molecules to absorb metal ions through electrostatic interaction and/or chelation.…”
Section: Zein Nanoribbons From Sheath Surfactant Solution Electrospinmentioning
confidence: 99%
“…The hydrophobicity of polysulfone polymers often leads to severe membrane fouling and decline of permeability through membranes. One way to overcome this drawback may be achieved by improving of hydrophilicity of membranes by blending the polymeric matrix with porous or non-porou inorganic fillers [6][7][8][9][10][11]. Among numerous inorganic fillers, silica, SiO 2 , in form of nonporous (nano)particles or as mesoporous material, is extensively used due to its facile preparation, mild reactivity and wellknown chemical properties [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…One way to overcome this drawback may be achieved by improving of hydrophilicity of membranes by blending the polymeric matrix with porous or non-porou inorganic fillers [6][7][8][9][10][11]. Among numerous inorganic fillers, silica, SiO 2 , in form of nonporous (nano)particles or as mesoporous material, is extensively used due to its facile preparation, mild reactivity and wellknown chemical properties [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Numerous examples of hybrid membranes incorporated with solid silica particles (SiO 2 ) have been reported and demonstrated that the addition of SiO 2 into polymer film is beneficial to membrane separation performance either in terms of membrane flux or selectivity [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%